Impacts of invasive tree species Bellucia pentamera on plant diversity, microclimate and soil of secondary tropical forest in West Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Solfiyeni, Syamsuardi, Chairul, Mukhtar E. 2022. Impacts of invasive tree species Bellucia pentamera on plant diversity, microclimate and soil of secondary tropical forest in West Sumatra, Indonesia. Biodiversitas 23: 3135-3146. The invasion of alien species in a region can alter species diversity. Bellucia pentamera Naudin is considered an alien invasive plant that has spread from Mexico to tropical America, and it is now invading some areas in Indonesia, including the tropical forest of Sumatra. Yet, the effects of its invasion on vegetation and the abiotic environment are not yet well understood. The objective of this study was to investigate the impacts of B. pentamera on species diversity and structure of vegetation, and microclimate and soil conditions of secondary tropical forests in West Sumatra. Vegetation analysis was conducted in secondary forest Bukit Tengah Pulau, South Solok, with three levels of dominance of B. pentamera namely: site 1 and 2 (60% and 16% dominance of B. pentamera respectively) and site 3 (no individual of B. pentamera). Sampling was conducted using a nested plot to collect data for tree, sapling and understorey vegetation for each site. The results showed the total number of tree species at sites 1, 2, and 3 were 23 species, 46 species, and 74 species respectively. For sapling, 20 species were found at site 1, 31 species at site 2, and 58 species at site 3. For understorey plants, 13, 16 and 36 species were detected at site 1, 2 and 3 respectively. The number of species at tree and sapling levels differed significantly among sites. The basal area also differed significantly among sites but not for sapling level. Site 1 was dominated by B. pentamera with Important Value Index (IVI) 130.8%), followed by Croton argyratus (27.63%), and Ficus variegata (26.47%). At site 2, B. pentamera dominated with IVI of 33.68%, followed by Lepisanthes sp. (20.01%) and Sizygium sp. (14.44%). Site 3 was dominated by Palaquium warsurifolium with IVI of 21.15% followed by Croton argyratus (20.02%) and Macaranga hypoleuca (13.21%). Diversity index (H') for tree-level was moderate at site 1 (H' = 1.78) and high at sites 2 and 3 (H' = 3.48 and 4.05). Similarly, the index for sapling was moderate at site 1 (H'= 2.12) and high at sites 2 and 3 (H'= 3.22 and 3.84). For understorey, the diversity index was low at site 1 (H'= 0.82) and moderate at sites 2 and 3 (H'= 1.8 and 2.86). Sites invaded by B. pentamera had a lower soil water content and higher temperature and light intensity, although they had higher nitrogen and phosphorus contents. Our findings suggest that the invasion of B. pentamera had negative impacts on plant biodiversity and microclimate, yet the impact was not clear cut on the soil.